Pediatric surgery - Adzick, N. Scott; Coran, Arnold G. (Philadelphia, PA : Elsevier/Saunders, 2012)
Pediatric Surgery, 7th Edition - edited by Arnold G. Coran, Anthony Caldamone, N. Scott Adzick, Thomas M. Krummel, Jean-Martin Laberge, and Robert Shamberger - features comprehensive, up-to-date guidance on all aspects of childhood surgery, including congenital malformations, tumors, trauma, and urologic problems. Apply the latest developments in fetal surgery, adolescent bariatric surgery, minimally invasive surgery in children, and tissue engineering for the repair of congenital anomalies, such as the separation of conjoined twins. you can also access the fully searchable text online at www.expertconsult.com, making this definitive resource more accessible than ever. Get comprehensive coverage of cutting-edge technology in pediatric surgical diseases, including imaging concepts, minimally invasive techniques, robotics, diagnostic and therapeutic advances, and molecular biology and genetics. Find information quickly and easily with an intuitive organization by body region and organs. Apply the guidance of world-renowned experts in pediatric surgery.
Part I. GENERAL -- 1 History of Pediatric Surgery: A Brief Overview -- 2 Molecular Clinical Genetics and Gene Therapy -- 3 Impact of Tissue Engineering in Pediatric Surgery -- 4 Advanced and Emerging Surgical Technologies and the Process of Innovation -- 5 Prenatal Diagnosis and Fetal Therapy -- 6 Neonatal Physiology and Metabolic Considerations -- 7 Respiratory Physiology and Care -- 8 Extracorporeal Life Support for Cardiopulmonary Failure -- 9 Neonatal Cardiovascular Physiology and Care -- 10 Sepsis and Related Considerations -- 11 Surgical Implications of Hematologic Disease -- 12 Nutritional Support in the Pediatric Surgical Patient -- 13 Pediatric Anesthesia -- 14 Clinical Outcomes Evaluation and Quality Improvement -- 15 Ethical Considerations -- 16 Patient- and Family-Centered Pediatric Surgical Care Part II . TRAUMA -- 17 Injury Prevention -- 18 Infants and Children as Accident Victims and Their Emergency Management -- 19 Thoracic Injuries -- 20 Abdominal Trauma -- 21 Genitourinary Tract Trauma -- 22 Musculoskeletal Trauma -- 23 Hand, Soft Tissue, and Envenomation Injuries -- 24 Central Nervous System Injuries -- 25 Vascular Injury -- 26 Burns -- 27 Child Abuse and Birth Injuries -- Part III. MAJOR TUMORS OF CHILDHOOD -- 28 Principles of Pediatric Oncology, Genetics of Cancer, and Radiation Therapy -- 29 Biopsy Techniques for Children with Cancer -- 30 Wilms' Tumor -- 31 Neuroblastoma -- 32 Nonmalignant Tumors of the Liver -- 33 Malignant Liver Tumors -- 34 Pediatric Gastrointestinal Tumors -- 35 Diagnosis and Treatment of Rhabdomyosarcoma -- 36 Other Soft Tissue Tumors -- 37 Teratomas and Other Germ Cell Tumors -- 38 Hodgkin Lymphoma and Non-Hodgkin Lymphoma -- 39 Ovarian Tumors -- 40 Testicular Tumors -- 41 Adrenal Tumors -- 42 Tumors of the Lung and Chest Wall -- 43 Bone Tumors -- 44 Brain Tumors -- Part IV . TRANSPLANTATION -- 45 Principles of Transplantation -- 46 Renal Transplantation -- 47 Pancreas and Islet Cell Transplantation -- 48 Liver Transplantation -- 49 Pediatric Intestinal Transplantation -- 50 Heart Transplantation -- 51 Pediatric Lung Transplantation -- 52 Surgical Implications Associated with Pediatric Bone Marrow Transplantation -- Part V. HEAD AND NECK -- 53 Craniofacial Anomalies -- 54 Understanding and Caring for Children with Cleft Lip and Palate -- 55 Otolaryngologic Disorders -- 56 Salivary Glands -- 57 Lymph Node Disorders -- 58 Childhood Diseases of the Thyroid and Parathyroid Glands -- 59 Neck Cysts and Sinuses -- 60 Torticollis -- VOLUME TWO Part VI . THORAX -- 61 Disorders of the Breast -- 62 Congenital Chest Wall Deformities -- 63 Congenital Diaphragmatic Hernia and Eventration -- 64 Cysts of the Lungs and Mediastinum -- 65 Lesions of the Larynx, Trachea, and Upper Airway -- 66 Infections and Diseases of the Lungs, Pleura, and Mediastinum -- 67 Esophagoscopy and Diagnostic Techniques -- 68 Esophageal Rupture and Perforation -- 69 Congenital Anomalies of the Esophagus -- 70 Caustic Strictures of the Esophagus -- 71 Esophageal Replacement -- 72 Disorders of Esophageal Function -- 73 Gastroesophageal Reflux Disease -- Part VII. ABDOMEN -- 74 Disorders of the Umbilicus -- 75 Congenital Defects of the Abdominal Wall -- 76 Inguinal Hernias and Hydroceles -- 77 Undescended Testis, Torsion, and Varicocele -- 78 Hypertrophic Pyloric Stenosis -- 79 Peptic Ulcer and Other Conditions of the Stomach 80 Bariatric Surgery in Adolescents 81 Duodenal Atresia and Stenosis-Annular Pancreas -- 82 Jejunoileal Atresia and Stenosis -- 83 Meconium Ileus -- 84 Meckel Diverticulum -- 85 Intussusception -- 86 Disorders of Intestinal Rotation and Fixation -- 87 Other Causes of Intestinal Obstruction -- 88 Short Bowel Syndrome -- 89 Gastrointestinal Bleeding -- 90 Alimentary Tract Duplications -- 91 Mesenteric and Omental Cysts -- 92 Ascites -- 93 Polypoid Diseases of the Gastrointestinal Tract -- 94 Necrotizing Enterocolitis -- 95 Crohn's Disease -- 96 Ulcerative Colitis -- 97 Primary Peritonitis -- 98 Stomas of the Small and Large Intestine -- 99 Atresia, Stenosis, and Other Obstructions of the Colon -- 100 Appendicitis -- 101 Hirschsprung Disease -- 102 Intestinal Dysganglionosis and Other Disorders of Intestinal Motility -- 103 Anorectal Malformations -- 104 Other Disorders of the Anus and Rectum, Anorectal Function -- 105 The Jaundiced Infant: Biliary Atresia -- 106 Choledochal Cyst -- 107 Gallbladder Disease and Hepatic Infections -- 108 Portal Hypertension -- 109 The Pancreas -- 110 The Spleen -- Part VIII . GENITOURINARY DISORDERS -- 111 Renal Agenesis, Dysplasia, and Cystic Disease -- 112 Renal Fusions and Ectopia -- 113 Ureteropelvic Junction Obstruction -- 114 Renal Infection, Abscess, Vesicoureteral Reflux, Urinary Lithiasis, and Renal Vein Thrombosis -- 115 Ureteral Duplication and Ureteroceles -- 116 Disorders of Bladder Function -- 117 Reconstruction of the Bladder and Bladder Outlet -- 118 Incontinent and Continent Urinary Diversion -- 119 Megaureter and Prune-Belly Syndrome -- 120 Bladder and Cloacal Exstrophy -- 121 Hypospadias -- 122 Abnormalities of the Urethra, Penis, and Scrotum -- 123 Disorders of Sexual Development -- 124 Abnormalities of the Female Genital Tract -- Part IX. SPECIAL AREAS -- 125 Vascular Anomalies -- 126 Pediatric Arterial Diseases -- 127 Congenital Heart Disease and Anomalies of the Great Vessels -- 128 Management of Neural Tube Defects, Hydrocephalus, Refractory Epilepsy, and Central Nervous System Infections -- 129 Major Congenital Orthopedic Deformities -- 130 Congenital Defects of the Skin and Hands -- 131 Conjoined Twins.
Includes index.;Expert consult - online and print--P. [4] of cover.
Keywords: Surgical Procedures, Operative; Child; Infant